The Influence of Hospital Management Information Systems on Administrative Efficiency: Literature Study - Andi Rahmat Reski; A. Aan B Syaputra; Liskha Ayuningrum; Nurul Alrahmi; M Awaluddin (Universitas Cahaya Prima, 2025)
This study aims to analyze the influenceHospital Management Information System (SIMRS) to administrative efficiencythrough the approachliterature studyThe study was conducted by reviewing five national scientific articles published between 2020 and 2025 that were relevant to the topic of hospital administration efficiency. The synthesis of results shows that the implementation of SIMRS plays a significant role in accelerating service processes, improving data accuracy, facilitating inter-unit coordination, and supporting faster and more effective decision-making.Overall, the results of the study show that the effectiveness of SIMRS implementation is highly dependent onmanagement support, technological readiness, and workforce training.With optimal management, SIMRS has proven to be a strategic tool for improving administrative efficiency, transparency, and the quality of hospital services in the digital era.